2018
DOI: 10.1007/s13205-018-1110-9
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive properties of Chamaerops humilis L.: antioxidant and enzyme inhibiting activities of extracts from leaves, seeds, pulp and peel

Abstract: In this work we evaluated methanolic extracts from different parts (leaves, seeds, fruit peel and pulp) of L. for antioxidant activity and the ability to inhibit enzymes linked with neurodegenerative diseases: acetylcholinesterase (AChE), butyrylcholinesterase (BChE) and tyrosinase (TYR). The total content of phenolics, flavonoids and condensed tannins was also determined. The antioxidant and inhibitory activities of the extracts varied significantly according to the tissue. Seed extracts showed the greatest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Phytochemical research on PES leaves has revealed the functions of 4 flavonoids and their working mechanisms [7]. Flavonoids are thought to be biologically active natural products present in a variety of fruits, vegetables, grains, and other dietary supplements [8][9][10]; flavonoids have attracted substantial attention because of their antioxidant abilities, chemopreventive properties, and radical scavenging activities, as well as cardiovascular protective, anti-inflammatory, and antiviral effects [11][12][13][14][15][16][17]. There is a growing interest in the analysis and identification of the flavonoid constituents of medicinal plants to identify the structure-activity relationship of flavonoids, as a small difference in the structure of a flavonoid can cause significant changes in its biological activities [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical research on PES leaves has revealed the functions of 4 flavonoids and their working mechanisms [7]. Flavonoids are thought to be biologically active natural products present in a variety of fruits, vegetables, grains, and other dietary supplements [8][9][10]; flavonoids have attracted substantial attention because of their antioxidant abilities, chemopreventive properties, and radical scavenging activities, as well as cardiovascular protective, anti-inflammatory, and antiviral effects [11][12][13][14][15][16][17]. There is a growing interest in the analysis and identification of the flavonoid constituents of medicinal plants to identify the structure-activity relationship of flavonoids, as a small difference in the structure of a flavonoid can cause significant changes in its biological activities [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1, it showed 31.65% for the methanol and 30.19 % for the water extract inhibitory activity against BChE. Some studies have reported the anti-cholinesterase activity due to the presence of active compounds including flavonoids, tannins, alkaloids, quinins, stilbens and xanthons (Pinho et al, 2013, Silva et al, 2014Gonçalves et al, 2018). Contrariwise, no extracts from the leave have shown any inhibition against acetyl and butyrylcholinesterase enzyme.…”
Section: Antioxidant Properties Of Different Extractsmentioning
confidence: 94%
“…In traditional medicine, C. humilis has been used in several diseases particularly for digestive system disorders (Benmehdi et al, 2012) and in gallstones and liver diseases (El-Hilaly et al, 2003). In addition, some compounds of extracts of Chamaerops have been reported to possess antioxidant (Benahmed- Bouhafsoun et al, 2013, Ben-messaoud et al, 2014, Gonçalves et al, 2018 hypolipidemic and hypoglycemic (Gaamoussi et al, 2010), antilithic (Beghalia et al, 2008) urinary antiseptic and anti-inflammatory (Bellakhdar et al,1991) and anticholinesterase (Gonçalves et al, 2018) activities. Besides its medicinal importance, Chamaerops presents an ecologically important role, it provides protection against erosion (Khoudali et al, 2014) since it allows attachment of the soil and fight against desertification.…”
Section: Introductionmentioning
confidence: 99%
“…This observation is in support of the previous report. 29 The facility and feasibility of extract preparation by decoction in households are the main reasons for the popularity of this method. In contrast, storage of prepared extracts is not feasible for a long period in the absence of adequate storage conditions which may induce intoxications.…”
Section: Distribution Of Chamaerops Humilis L Preparation Methodsmentioning
confidence: 99%